Wushenziye Formula Improves Skeletal Muscle Insulin Resistance in Type 2 Diabetes Mellitus via PTP1B-IRS1-Akt-GLUT4 Signaling Pathway. (31st December 2017) - Tian, Chunyu; Chang, Hong; La, Xiaojin; Li, Ji-an
Abstract : Background. Wushenziye formula (WSZYF) is an effective traditional Chinese medicine in the treatment of type 2 diabetes mellitus (T2DM). Aim. This study aimed to identify the effects and underlying mechanisms of WSZYF on improving skeletal muscle insulin resistance in T2DM. Methods. An animal model of T2DM was induced by Goto-Kakizaki diabetes prone rats fed with high fat and sugar for 4 weeks. Insulin resistance model was induced in skeletal muscle cell. Results. In vivo, WSZYF improved general conditions and decreased significantly fasting blood glucose, glycosylated serum protein, glycosylated hemoglobin, insulin concentration, and insulin resistance index of T2DM rats. In vitro, WSZYF enhanced glucose consumption in insulin resistance model of skeletal muscle cell. Furthermore, WSZYF affected the expressions of molecules in regulating T2DM, including increasing the expressions of p-IRS1, p-Akt, and GLUT4, reducing PTP1B expression. Conclusion . These findings displayed the potential of WSZYF as a new drug candidate in the treatment of T2DM and the antidiabetic mechanism of WSZYF is probably mediated through modulating the PTP1B-IRS1-Akt-GLUT4 signaling pathway.